Analisis Perhitungan Full Costing Pisang Crispy “Loka” Surabaya - Wahyu Surya Kartika Dewi; Desipradani, Gita (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
The full costing approach is used in this study to examine the production costs of Crispy Banana "LOKA" Surabaya. A quantitative methodology based on documents and interviews is used in this study. The results of the study show that the full costing method provides a more detailed picture by allocating all production costs (fixed and variable), and also separating additional costs for each flavor variant, thus finding different cost per box for each variant such as chocolate variant of Rp14,726, cheese variant of Rp16,909, tiramisu variant of Rp14,859, milo variant of Rp15,959, green tea variant of Rp14,859, palm sugar variant of Rp14,859 and mix variant of Rp14,884.